Localization of the delta-like-1-binding site in human Notch-1 and its modulation by calcium affinity. - Cordle, J; Redfieldz, C; Stacey, M; Van Der Merwe, P; Willis, A; Champion, B; Hambleton, S; Handford, P (2008)
The Notch signaling pathway plays a key role in a myriad of cellular processes, including cell fate determination. Despite extensive study of the downstream consequences of receptor activation, very little molecular data are available for the initial binding event between the Notch receptor and its ligands. In this study, we have expressed and purified a natively folded wild-type epidermal growth factor-like domain (EGF) 11-14 construct from human Notch-1 and have used flow cytometry and surface plasmon resonance analysis to demonstrate a calcium-dependent interaction with the human ligand Delta-like-1. Site-directed mutagenesis of three of the calcium-binding sites within the Notch-(11-14) fragment indicated that only loss of calcium binding to EGF12, and not EGF11 or EGF13, abrogates ligand binding. Further mapping of the ligand-binding site within this region by limited proteolysis of Notch wild-type and mutant fragments suggested that EGF12 rather than EGF11 contains the major Delta-like-1-binding site. Analysis of an extended fragment EGF-(10-14), where EGF11 is placed in a native context, surprisingly demonstrated a reduction in ligand binding, suggesting that EGF10 modulates binding by limiting access of ligand. This inhibition could be overcome by the introduction of a calcium binding mutation in EGF11, which decouples the EGF-(10-11) module interface. This study therefore demonstrates that long range calcium-dependent structural perturbations can influence the affinity of Notch for its ligand, in the absence of any post-translational modifications.